Síntese de titanatos alcalinos e avaliação na transesterificação catalítica - Marciniuk, Letícia Ledo (2012)
Three methods for the synthesis of sodium titanates were investigated: solid state treatment (800 oC), hydrothermal treatment (110 oC) and sol-gel method (55 oC). The titanium oxide was used as starting compound for xerothermal and hydrothermal treatments. The titanium (IV) n-butoxide was used in the sol-gel method. The samples were characterized by X-ray diffraction, energy-dispersive X-ray, atomic absorption spectroscopy, scanning electron microscopy, thermogravimetry coupled to mass spectroscopy, nitrogen physisorption, Raman spectroscopy, X-ray photoelectron spectroscopy (XPS). The materials synthesized were used as heterogeneous-basic catalysts in the transesterification reaction between ethyl acetate and methanol, performed under mild conditions: 50 oC, 30 min of reaction time, 4 wt. % of catalyst and molar ratio of ester:alcohol 1:6. The solid prepared by sol-gel method was the most active leading to esters yields around 30 %. This non-calcined material showed high catalytic stability. The loss of activity on the fourth cycle was accompanied by the appearance of a new species of oxygen, identified using XPS analysis. The XPS spectrum showed that the basic character of this oxygen species was inferior to that of the original species, which could explain the loss of catalytic activity. The deactivation was accompanied by the intensification of a second Na 1s component at higher binding energy. The migration of these ions to the catalyst surface reduced their availability for the formation of active Ti-O-Na+ sites, which explain the loss of catalytic activity after the fourth test cycle or after calcination of the material, both of which resulted in the same effect.